Estimation of the primary stability of the press-fit and screwed-in acetabular components after hip joint arthroplasty - Loskutov, Oleg; Naumenko, Nadiia; Loskutov, Oleksandr; Syniehubov, Dmytro; Gorobets, Dmytro; Furmanova, Kseniya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Arthroplasty is one of the most common and effective treatments for degenerative diseases and injuries of the hip joint, but marked increase in the number of revision procedures associated with instability of the implant, including cups, and a pair of friction problems. Objective: using biomechanical methods to evaluate the primary acetabular stability with screwing up and press-fit components. Methods: to evaluate the stress-strain state and subchondral spongy tissues in the acetabular zone under load of 1000 H, developed a simplified design scheme of the hip joint and healthy model of «bone – cup – insert – head» implant using finite element method. Press-fit and that screwing up cups were studied. Results: in healthy hip joint any stress concentrators are absent. Maximum values are 0.09 MPa stress-strain state on the strength of spongy bone tissue 12.17 MPa. The most strenous share of subchondral bone is part of the roof — 16.24 MPa for her strength of 150–200 MPa. If using press-fit cups revealed increasing tension of spongy tissue in 4 ÷ 5 times, and at the entrance to the subchondral acetabular zone — 2 ÷ 3 times. With the use of screw up cups t transferring the load on the pelvic bone closest to the healthy joint. Small local stress concentrators in the spongy tissue occur in the contact zone of the threaded subchondral and spongy tissue and at a distance of 1mm their value is reduced by 2–3 times and does not exceed 0.3 MPa. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> the use of screw up cup has advantages, especially in osteoporosis, because after implantation load on the pelvic bone close to the stress-strain state of healthy hip joint.